X-linked hypophosphatemic rickets: from diagnosis to management - Eujin Park; Hee Gyung Kang (The Korean Pediatric Society, 2024)
X-linked hypophosphatemia (XLH), the most common cause of hypophosphatemic rickets, affects one in every 20,000 people. Although conventional therapy for XLH was introduced approximately 4 decades ago, the temporary replacement of oral phosphate salts and activated vitamin D cannot completely control chronic hypophosphatemia, leaving patients with incomplete healing and residual skeletal deformity as well as at risk of endocrine abnormalities and adverse drug reactions. However, understanding the pathophysiology has led to the development of a targeted therapy, burosumab, a fibroblast growth factor-23 inhibitor that was recently approved in Korea for the treatment of XLH. This review provides insight into the diagnosis, evaluation, treatment, and recommended follow-up for a typical case of XLH and reviews its pathophysiology.